Forma wyrażenia zgody małżeńskiej określona w kan. 1104 § 1-2 KPK - Dzierżon, Ginter (Ius Matrimoniale, 2017)
The analyses of the current legal order show that for a marriage to become contracted validly the contracting parties need to be present together or may enter into marriage by proxy (proxies). Naturally, for a marriage to be valid it is insufficient to express matrimonial consent in the internal sphere only; it is necessary to externalize the consent with the aim of its social verification45 but also because of the dignity of the other party to whom a nupturient is willing to give himself. Canonists agree that according to the natural law matrimonial consent in its external sphere could be expressed in any possible way. However, in the ecclesiastical order the legislator did not allow this kind of latitude and specified the forms of expression of matrimonial consent (as discussed in can. 1104 § 1-2 CIC). In an ordinary situation, if both nupturients can speak, they should contract a marriage in words although meeting this requirement is not necessary for the validity but rather for the fairness of the act. However, in extraordinary conditions, when at least one person cannot speak, it is possible to express one’s consent through equivalent signs. Silence nonetheless does not meet the criteria discussed here since in this hypothesis one’s will remains inertial and, as a result, a legal act does not attain effectivity in the system.